TEACHERS’ PERCEPTION OF HEALTH PROBLEMS OF HIV AND AIDs ORPHANS AND VULNERABLE CHILDREN IN AGBANI EDUCATION ZONE OFENUGU STATE - Nnamani, M.N.; Ejike, F.C. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
The Study was aimed at determining the level of teachers ’perception of health problems of HIVIAids Orphans and vulnerable children (OVC) in Agbani Education Zone of Enugu State. In line with the purpose of the study, four research questions and two null hypotheses were postulated. Related literature were reviewed and summarized. Descriptive survey research design. was adopted. The sample for the study consisted of 3.63 out of 1073 teachers from 8 out of 63 government-owned secondary schools in Agbani Education Zone of Enugu State. Data were gathered by means of structured questionnaire. Reliability of the instrument was established by exposing the structured questionnaire twice using test-retest method. The results were subjected to testing for reliability coefficient using Pearson Product Moment Correlation Coefficient (PPMCC) which yielded high positive correlation of.82. Data obtained were analysed using frequencies and percentages for research questions 1 to 3; and the mean statistic was used to analyse research question 4. Null Hypothesis 1was tested using the chi-square statistics while null hypothesis 2 was tested using the t-test statistic. 4 The findings showed that teachers in Agbani Education zone have high level perception of the health problems of HIV and AIDs OVC but perceived to a low extent their coping strategies. Tested hypotheses revealed that· teachers’ perception of health problems of HIV and AIDS OVC, and their coping strategies were not influenced by location. Based on the findings; implications of the study, conclusion and recommendations were made; including that: extended family members, government and NGOs should provide counselling; and psychological support by ensuring HIV and AIDS OVCs enrolment in schools; access to shelter; good nutrition, health and social services.